A review of promising candidate reactions for chemical heat storage. (March 2015) - Yan, T.; Wang, R.Z.; Li, T.X.; Wang, L.W.; Fred, Ishugah T.
Abstract: Thermal energy storage is a necessary technology for the application of renewable energy and low-grade thermal energy. Chemical heat storage has been proved to be a feasible and promising method to store thermal energy. As compared to other thermal energy storage methods, chemical heat storage exhibits high energy storage density as well as feasibility for long-duration energy storage. In this paper, the basic principle of the chemical heat storage is firstly elaborated. Then the selection criteria of the chemical reaction are given. The aim of this review is to provide an insight into the promising candidate reactions for chemical heat storage application. The associated reversible chemical reactions available for thermal energy storage systems are summarized. Ongoing research and development studies illustrate that chemical heat storage is a very favorable option for the different application when diverse promising candidate reactions are selected. As working temperature is one of the key parameters for thermal energy storage systems, emphasis is given to the judgment of application temperature range for chemical heat storage. The determination of applicative temperature range of reversible chemical reactions is discussed. Besides, the challenge and prospect of the chemical heat storage technology are analyzed in the paper.